2021
DOI: 10.1016/j.hjdsi.2020.100508
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for responding to the COVID-19 pandemic in a rural health system in New York state

Abstract: Research and media reports about coronavirus disease 2019 (COVID-19) have largely focused on urban areas due to their high caseloads. However, the COVID-19 pandemic presents distinct and under-recognized challenges to rural areas. This report describes the challenges faced by Bassett Healthcare Network (BHN), a health network in rural upstate New York, and the strategies BHN devised in response. The response to COVID-19 at BHN focused on 4 strategies: (1) Expansion of intensive-care capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…At this time, strong leadership is very important, but flexibility is also essential to ensure that every regulation is not conducted by force ( Beilstein et al, 2020 ). Aron et al (2021) showed (as seen in Fig. 5 ) that there are some strategies to handle the pandemic.…”
Section: Covid-19 In Indonesiamentioning
confidence: 92%
“…At this time, strong leadership is very important, but flexibility is also essential to ensure that every regulation is not conducted by force ( Beilstein et al, 2020 ). Aron et al (2021) showed (as seen in Fig. 5 ) that there are some strategies to handle the pandemic.…”
Section: Covid-19 In Indonesiamentioning
confidence: 92%
“…In sum, the literature to date indicates there is still much to be done to support diverse women and gender-diverse individuals in their leadership journeys. Several studies have discussed the practice of allyship in health care (Spector and Overholser, 2022;Aron et al, 2021). What remains neglected is the lived experiences of those who have been marginalized and those who have undertaken the work of allyship, sharing successes as well as failures.…”
Section: Edi 423mentioning
confidence: 99%
“…In sum, the literature to date indicates there is still much to be done to support diverse women and gender-diverse individuals in their leadership journeys. Several studies have discussed the practice of allyship in health care (Spector and Overholser, 2022; Aron et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…12,13 Since the inception of the pandemic, most hospitals, including the rural hospitals of focus in the study, have taken on a leadership role, not only in the clinical management and rehabilitation of patients with COVID-19 but also in other response efforts, including crisis communication efforts, COVID-19 vaccination, and community health education and promotion. 14,15 Did such activities lead to an increase in rural hospitals' visibility and their perceived value in rural communities? Did community perceptions about rural hospitals improve?…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic highlighted the importance of having emergency and acute care services close to home and allowed many rural hospitals to collaborate with their local communities in pandemic response efforts 12,13 . Since the inception of the pandemic, most hospitals, including the rural hospitals of focus in the study, have taken on a leadership role, not only in the clinical management and rehabilitation of patients with COVID‐19 but also in other response efforts, including crisis communication efforts, COVID‐19 vaccination, and community health education and promotion 14,15 . Did such activities lead to an increase in rural hospitals’ visibility and their perceived value in rural communities?…”
Section: Introductionmentioning
confidence: 99%